1988
DOI: 10.1073/pnas.85.16.5879
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering of antibody binding sites: recovery of specific activity in an anti-digoxin single-chain Fv analogue produced in Escherichia coli.

Abstract: A biosynthetic antibody binding site, which incorporated the variable domains of anti-digoxin monoclonal antibody 26-10 in a single polypeptide chain (Mr = 26,354), was produced in Escherichia cofi by protein engineering. This variable region fragment (Fv) analogue comprised the 26-10 heavy-and light-chain variable regions (VH and VL) connected by a 15-amino acid linker to form a single-chain Fv (sFv). The sFv was designed as a prolyl-VH-(linker)-VL sequence of 248 amino acids. A 744-base-pair DNA sequence cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
737
0
12

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,363 publications
(755 citation statements)
references
References 49 publications
6
737
0
12
Order By: Relevance
“…15,16 In scFv constructs, the carboxy terminus is joined to the amino terminus of variable domains by a Ln of appropriate length and flexibility. Therefore, the scFv can be constructed at least in two different configurations, either VHLnVL or VLLnVH.…”
Section: Construction Of Plasmid Vectors Encoding Single -Chain Variamentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 In scFv constructs, the carboxy terminus is joined to the amino terminus of variable domains by a Ln of appropriate length and flexibility. Therefore, the scFv can be constructed at least in two different configurations, either VHLnVL or VLLnVH.…”
Section: Construction Of Plasmid Vectors Encoding Single -Chain Variamentioning
confidence: 99%
“…Therefore, the scFv can be constructed at least in two different configurations, either VHLnVL or VLLnVH. 15 These two different orientations of domains may distort native conformation of the antigenbinding site of scFv. We have previously shown that for the best antigen mimicry of scFv derived from 3H1 Ð an antiidiotype antibody mimicking carcinoembryonic antigen Ð the VH chain should be in the amino terminus of the scFv; VH and VL should be linked by a 15 -amino acid Ln.…”
Section: Construction Of Plasmid Vectors Encoding Single -Chain Variamentioning
confidence: 99%
See 1 more Smart Citation
“…A major outcome of these advances is the ability to generate very small and functional antibody fragments, such as scFvs. [13][14][15] Moreover, using antibody phage display libraries, it is possible to isolate new recombinant scFv antibodies with the desired specificity and affinity directed toward a large array of antigens. 16 Our aim was to explore the possibility of using a small recombinant scFv antibody molecule for the modulation and reversal of the MDR phenotype in tumor cells by direct inhibition of Pgpmediated drug-efflux activity.…”
mentioning
confidence: 99%
“…As a delivery system the smaller single chain antibody (SCA), comprising linked variable heavy (VH) and variable light (VL) chain antibody domains shows great promise (Huston et al, 1988). Where tested SCAs demonstrate good tissue penetration (Yokota et al, 1992), rapid renal clearance of non-localised protein and potentially low immunogenicity (Colcher et al, 1990).…”
mentioning
confidence: 99%